(untitled) (Homoeopathy for All, 2025)
Dr. Wilhelm Heinrich Schuessler introduced the Biochemic system of medicine or tissue remedies which are homoeopathically prepared from mineral salts. Biochemic medicines have an effect at the physiological level. The World Health Organization defines this biochemical medicine method as inorganic cellular salt therapy. It is one of the complementary therapies introduced as a tissue salt remedy. These nutrients help regulate cellular functions and support health by regulating cellular salt levels. These tissue remedies are made by adding a minimal amount of tissue salt. The biochemical tissue remedies are inorganic tissue salts. There are a total of twelve biochemic tissue remedies which have their own individual properties.